Use of Narrow Band Imaging (NBI) as a non-invasive adjunct for margin assessment in oral squamous cell carcinoma (OSCC) - Krishnasamy Nitya; Yash Merchant; Somdipto Das; Sameep S. Shetty (Oral Oncology Reports)
The status of margins in OSCC is a critical prognostic factor that is known to influence local recurrence and overall survival outcomes. Positive or close surgical margins substantially increase the risk of locoregional failure, necessitating revision and adjuvant therapy that may adversely impact patients’ quality of life. Conventional intraoperative techniques of assessment of margins such as visual inspection, palpation, and selective frozen section analysis, have inherent limitations. These include subjectivity, sampling errors, and procedural delays. Narrow Band Imaging (NBI) is an innovative, non-contact, non-invasive optical imaging modality that enhances visualisation of the mucosal and submucosal microvasculature by employing filtered light at specific wavelengths. NBI enables more accurate delineation of tumour margins by accentuating vascular patterns associated with neoplastic transformation. This short correspondence discusses the fundamental principles, intraoperative applications, clinical advantages, and prospects of NBI as a valuable adjunct to conventional methods for margin assessment.